CFD based synergistic analysis of wind turbines for roof mounted integration. Issue 156 (September 2016) - Larin, P.; Paraschivoiu, M.; Aygun, C.
Abstract: The increasing global demand for energy and environmental concerns have provoked a shift from exhaustible, fossil fuel based energy to renewable energy sources. It is clear that wind energy will play an important role in satisfying our current and future energy demands. In this paper, a horizontal configuration of a Savonius wind turbine is proposed to be mounted on the upstream edge of a building, in such a way that its low performance is improved by taking advantage of the flow acceleration generated by the edge of the building. The importance of integrated simulations which include both the building and the turbine is shown and it is also demonstrated that the individual calculations of the flow around the building and the turbine individually cannot be superposed. Following the validation of our methodology with experimental data, we calculate the performance of the Savonius wind turbines placed in the vicinity of the edge of the building top. The position, blade number, and circumferential length are then investigated when the turbine is mounted on a building. The objective is to better understand wind turbine behavior for low speed urban environments. The flow fields of conventional Savonius and cup type turbines are solved using Computational Fluid Dynamics (CFD) in 3D domains. The optimal configuration shows an improvement in the power coefficient from 0.043 to 0.24, representing an improvement of 450%. The improvement also demonstrates that although cup type blades show very poor performance in free stream flow, they perform well in the right environment. Highlights: Validation of Power Coefficient calculation from CFD for a Savonius turbine. Analysis of the flow around a building mounted Savonius turbine. Demonstration that Savonius turbines are inefficient when installed on buildings. Developed of a drag based turbine that works in synergy with the building aerodynamics.